Individual and Temporal Variation in Use of Residential Areas by Urban Coyotes - Thompson, Connor A.; Malcolm, Jay R.; Patterson, Brent R. (Frontiers in Ecology and Evolution, 2021)
Coyotes (Canis latrans) have established populations in most major urban centers across North America. While the risk of attacks on humans or their pets is low, the presence of carnivores in areas with high human use has resulted in increased public concern. Having a clearer understanding of which animals are more likely to interact with humans and when interactions are more likely to occur will help mitigate conflicts. Despite clear patterns of human avoidance, human-coyote interactions occur most frequently in residential areas. Our purpose was to determine if use of residential areas varied consistently across individuals or time. We used locations from GPS collars deployed on 14 coyotes in the Greater Toronto Area, Ontario, Canada from 2012-2017 to fit a step selection function. Average (± SE) home range size estimates were 17.3 ± 4.6 km2 for resident coyotes and 102.8 ± 32.9 km2 for non-residents. We found that coyotes used natural areas more (β = 0.07, SE = 0.02, p < 0.0001), and roads (β = −0.50, SE = 0.13, p < 0.0001) and residential areas (β = −0.79, SE = 0.21, p = 0.0001) less during the day than at night. We also found that coyotes were more likely to use residential areas in the breeding season from January – April (β = 0.69, SE = 0.20, p = 0.0007) and the pup rearing season from May – August (β = 0.54, SE = 0.13, p < 0.0001) than in the dispersal season from September – December. Lastly, we found that resident coyotes were less likely to use residential areas than non-resident coyotes (β = −1.13, SE = 0.26, p < 0.0001). As far as we are aware, our study is the first to identify the seasons when coyotes are more likely to use residential areas. The seasonal patterns in habitat use that we observed reflect patterns that have been previously reported for human-coyote conflicts. Our results demonstrate that reducing the availability of anthropogenic food sources in residential areas, particularly in the winter and spring, should be a priority for managers aiming to reduce human-coyote conflict in urban areas.